Performance evaluation of cascaded H-bridge multilevel inverter with hybrid controller based PV system - C. Dinakaran; T. Padmavathi (Institute of Advanced Engineering and Science, 2026)
Rising concerns about global warming demand renewable growth, which in turn needs efficient converter topologies to integrate renewable power. This article presents a single-phase, nine-level inverter to improve the performance of non-conventional power systems. Here, the foremost aim, based on the advanced techniques, to diminish the representation of switches with sources has been executed. This influences the appended preservation of generating energy against non-conventional power resources. This conquest during the statistic of switch refuses every switching loss, counting the cardinal-like driving circuit that details a minimization within convolution based on supervision track, consequently depreciating the disturbances with scope. The proposed inverter has a diminished production voltage total harmonic distortion (THD) with an ideal power factor. The cascaded H-bridge multilevel inverter (CHBMLI) topology is intended for the proposed method in support of the design, added ant-lion optimization (ALO) tuned fuzzy logic controller (FLC) methodical assessment for compensation. The presented arrangement is refined to diminish the energy losses, just as it is unified among reproducing systems that boost the smooth output voltage with reduced %THD. In addition, contraction in energy losses and amplification in efficiency are accomplished by producing transitional levels for the level elaboration system. Indeed, every completion related to the suggested arrangement is evaluated over the reproduction of MATLAB/Simulink and PROTEUS applications.